2016
DOI: 10.1186/s12889-016-3604-x
|View full text |Cite
|
Sign up to set email alerts
|

A randomised controlled trial of multiple periods of outdoor free-play to increase moderate-to-vigorous physical activity among 3 to 6 year old children attending childcare: study protocol

Abstract: BackgroundThe implementation of physical activity interventions in centre-based childcare services has been recommended to improve child health. This study aims to evaluate the efficacy of scheduling multiple periods of outdoor free play in increasing the time children spend in moderate-to-vigorous physical activity (MVPA) during childcare.MethodsThe study will employ a between group cluster randomised controlled trial design. Fourteen childcare services in the Hunter New England region of New South Wales, Aus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…The interventions involve: tailored written materials, videos, support coaching using brief MI, and community gatherings. Previous studies in child care have focused on intervention strategies such as food service [112, 114, 120] and curriculum changes [113, 122]; interventions directed toward center-based teachers, such as in-person training [110, 116, 125], non-tailored written materials [116, 119, 122, 125], academic detailing [119], and other types of technical assistance, and strategies that included parent and teacher modeling [121].…”
Section: Discussionmentioning
confidence: 99%
“…The interventions involve: tailored written materials, videos, support coaching using brief MI, and community gatherings. Previous studies in child care have focused on intervention strategies such as food service [112, 114, 120] and curriculum changes [113, 122]; interventions directed toward center-based teachers, such as in-person training [110, 116, 125], non-tailored written materials [116, 119, 122, 125], academic detailing [119], and other types of technical assistance, and strategies that included parent and teacher modeling [121].…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, only a few interventions have adopted a similar approach and the results remain ambiguous. Wolfenden and colleague’s [ 38 ] intervention divided the typical single 45-min bout of outdoor playtime afforded in Australian childcare centres into three shorter outdoor sessions of 15 min each; however, no results have been published to date. Similar to the SPACE intervention, Alhassan and colleagues [ 62 ] also implemented four 30-min outdoor play sessions in a small number of childcare centres in the United States.…”
Section: Discussionmentioning
confidence: 99%
“…The trial is reported in accordance with the CONSORT statement and its extension on cluster randomised trials [ 22 ]. A detailed protocol for this trial has been previously published [ 23 ].…”
Section: Methodsmentioning
confidence: 99%